Liver findings in patients with Carney complex, germline PRKAR1A pathogenic variants, and link to cardiac myxomas. Issue 6 (June 2020) - Tirosh, Amit; Hamimi, Ahmed; Faucz, Fabio; Aharon-Hananel, Genya; Zavras, Phaedon D; Bonella, Belen; Auerbach, Adi; Gillis, David; Lyssikatos, Charalampos; Belyavskaya, Elena; Stratakis, Constantine A; Gharib, Ahmed M
Abstract : This study aimed to evaluate liver involvement in patients with Carney complex (CNC) based on a large cohort and to analyze any germline PRKAR1A genotype–phenotype association of liver disease. The study included 83 patients with CNC, followed between 1995 and 2018 at a tertiary research center. We reviewed liver images, recorded types and number of lesions and analyzed per genotype: all patients were sequenced for the PRKAR1A gene. A total of 29/83 patients (24.0%) had liver radiological findings. Patients with liver lesion had a significantly higher rate of pathogenic variants detected in the PRKAR1A gene (72.4 vs 38.9%, P  = 0.005, respectively). Patients with a pathogenic variant detected on germline PRKAR1A analysis had a higher risk for having a liver lesion compared with patients with wild-type (WT) PRKAR1A alleles (21/42 (50.0%) vs 8/41 (19.5%), respectively, P  = 0.004). Among patients with liver lesions, those with a nonsense PRKAR1A pathogenic-variant had more liver lesions (7/7) than among those with other pathogenic-variant types (8/22, P  = 0.001). In multivariable analysis, detection of liver lesion(s) was associated with an odds ratio of 5.2 for cardiac myxomas (95% CI 1.55–17.49, P  = 0.008). In conclusion, patients with CNC, particularly with a PRKAR1A pathogenic variant, have a higher rate of liver lesions. Additionally, liver lesions are associated with a high risk for cardiac myxomas in this population.